The Research of Data Center Construction for Smart City. Issue 5 (April 2019) - Su, Junsheng
Abstract: Basic support is provided for system operation and analysis by Data Center, which is used as an important infrastructure of Smart City.Data Center is related to network, system integration, information security, data base, data mining, etc.the quality of Resource sharing and integration is influenced directly by construction effect of Data Center.The connotation and the composition of Data Center are researched, and according to the construction request of Data Center, a certain architecture of Smart City is put forward, and the content of data center is discussed, and the approach of construction idea is researched, and the application of data center for Smart City is discussed in this paper.